Venous thromboembolism and mortality in a multiethnic population: a report from the Birmingham Black Country VTE registry (BBC-VTE Investigators). (3rd October 2022) - Sanders, A; El-Bouri, W K; Lip, G Y H
Abstract: Background: Most epidemiological studies into venous thromboembolism (VTE) are based on the white Caucasian population and unrepresentative of VTE outcomes in non-white ethnicities. Purpose: Our VTE registry aims to get an insight into the outcomes of VTE patients as applicable to a developed world population with a multi-ethnic background. This will guide clinicians to make appropriate decisions with regards to management and prognosis. Methods: The Birmingham Black Country VTE Registry (BBC-VTE) is a multi-ethnic cohort of patients in the West Midlands region of the United Kingdom, who suffered a first episode of VTE. In this study we compared baseline characteristics, treatment patterns and outcomes, and secondly, compared these among the different ethnic groups in this region. Results: Between the years 2012–2014 there was a total of 1615 patients (mean age 65.5; 53.1% female) admitted with a first episode of VTE of whom, 134 (8.3%) were Asian, 92 (5.7%) Black, and 1213 (75.1%) White. Asian patients were younger (mean age 54, SD 19.3) vs Black patients (59, SD 19.7) and White patients (68, SD 17.4); and were less often female (50.7% vs. 55.4% and 53.8%) for Black and White patients respectively. The initial VTE event was a DVT in 680 (42.1%) and a PE±DVT in 935 patients (57.9%). Below-knee and above-knee DVT occurred in 95 (5.9%) and 585 (36.2%) patients respectively. Recurrent DVT occurred in 3.2% of those with an initial below-knee DVT and 12.5% of those with an initial above-knee DVT. Recurrent PE was also more common in those with an initial above knee DVT (4.8%) compared to those with below-knee DVT (3.2%). After the initial VTE event, 1269 (78.6%) were started on long-term anticoagulation for the prevention of recurrent VTE. Of those, 65.1% stayed on anticoagulation for up to 6 months after the initial VTE event, and 34.9% continued for longer than 6 months, including those on lifelong anticoagulation. Bleeding and major bleeding occurred in 6.8% and 2.5% respectively in those on anticoagulation for 6 or less months, vs. 10.4% and 3.5% in those anticoagulated for longer than 6 months. The most common site of bleeding was gastrointestinal in 42.3% of all bleeds and this site was also responsible for 54.3% of major bleeds. From evaluating the odds ratio for VTE mortality (see Fig. 1), ethnicity did not have a significant impact. Older age; the presence of diabetes mellitus; history of malignancy; as well as admission laboratory results for C-reactive protein and neutrophil count were all significantly associated with higher odds of mortality in this patient cohort. Conclusion: BBC-VTE is a contemporary multi-ethnic cohort of patients providing insights into the risk factors among multi-ethnic patients that have developed VTE. Ethnicity did not emerge as an independent risk for VTE mortality. Funding Acknowledgement: Type of funding sources: None.